Neurofilament light chain levels in cerebrospinal fluid as a sensitive biomarker for cerebral adrenoleukodystrophy - Toshiyuki Kakumoto; Takashi Matsukawa; Hiroyuki Ishiura; Harushi Mori; Shoji Tsuji; Tatsushi Toda (Annals of Clinical and Translational Neurology, 2023)
ABSTRACT Objective Adrenoleukodystrophy (ALD) has a poor prognosis when it progresses to the cerebral form (CALD). The aim of this study is to investigate whether cerebrospinal fluid (CSF) neurofilament light chain (cNfL) is a sensitive biomarker for detecting CALD and assessing response to hematopoietic stem cell transplantation (HSCT). Methods We conducted a cross‐sectional study of 41 male ALD patients. The cNfL levels in patients with the cerebral form of ALD (CALD) or the cerebello‐brainstem form of ALD were compared with those in patients with adrenomyeloneuropathy (AMN). The correlation between cNfL levels and MRI‐based Loes severity scores was investigated. A longitudinal analysis was performed on patients who underwent multiple CSF examinations. Results The cNfL levels in 22 patients with CALD were significantly higher than those in 14 patients with AMN (median, 5545 vs. 1490 pg/mL; p < 0.001). The cutoff cNfL level of 1930 pg/mL showed good sensitivity (95.5%) and specificity (85.7%) for distinguishing CALD from AMN. The cNfL levels were positively correlated with Loes scores (p < 0.001). The cNfL levels in three AMN patients who later converted to CALD increased above the cutoff level during the conversion period, while the cNfL levels in four patients who remained in AMN were consistently below the cutoff. In 10 ALD patients who underwent HSCT, their cNfL levels decreased 3–24 months after HSCT. Two patients whose cNfL increased after HSCT showed deterioration in cognitive functions. Interpretation The cNfL level is useful for evaluating the disease activities of ALD and the response to HSCT.